Case Report: Mutant SCN9A Susceptible to Charcot Neuroarthropathy in a Patient With Congenital Insensitivity to Pain - Xie, Xiao-hui; Tang, Jian-guang; Liu, Zhong-hua; Peng, Shui-jiao; Yuan, Zhuang-zhuang; Gu, Heng; Hu, Yi-qiao; Tan, Zhi-ping (Frontiers in Neuroscience, 2021)
Charcot neuroarthropathy is a systemic disease with pathological changes in the musculoskeletal system, which lead to fractures, dislocations, and deformities involving multiple bones and joints, particularly those of the foot. While the common underlying cause of Charcot neuroarthropathy is diabetes mellitus, it is also associated with congenital insensitivity to pain (CIP). CIP is a rare disorder caused by loss-of-function mutations in SCN9A encoding Nav1.7. Herein, we report a CIP patient from a consanguineous family susceptible to Charcot neuroarthropathy with a novel SCN9A mutation. A middle-aged man suffered from CIP, repeated painless fractures and developed bone and joint destruction. The physical and radiological examinations revealed that multiple joints were swollen and deformed, and soft-tissue trauma was evident. We identified a novel homozygous SCN9A mutation (p.Cys1339Arg) by whole-exome sequencing, which was verified using Sanger sequencing. In addition, the wild-type and mutated p. Cys1339Arg were assessed in HEK293 cells expressing Nav1.7, and the results showed that p. Cys1339Arg almost abolished the Nav1.7 sodium current. In conclusion, Charcot neuroarthropathy associated with CIP demonstrated a wider spectrum of Charcot neuroarthropathy than was previously recognized or documented. Additionally, this finding is conducive to understanding the critical amino acids for maintaining the function of Nav1.7, thus contributing to the development of Nav1.7-targeted analgesics.